Study on Roof Presplitting Mechanism and Deformation Control of Reused Roadway in Compound Soft Rock by Roof Presplitting Approach. (1st August 2022) - Qi, Fuzhou; Yang, Dangwei; Li, Xinming; Li, Bin; Zhai, Yingying; Yu, Shuisheng
Abstract : Based on the compound soft rock movement law, the rock formation structural features for a mining roadway were examined. Furthermore, the presplitting, extension, and coalescence mechanism of rock formation and the engineering needs for reusing an abandoned underground roadway were studied. According to engineering and geological conditions, an analytic expression of the inertial force, the moment of inertia, and the vertical stress acting on the breakage are obtained by constructing a structural mechanical model of the overlying strata. The transfixion law, the tensile shear failure characteristics, the release rate in the fracture expansion process of presplitting fissures, and the evolution law of the plastic zone in reused roadway surrounding rock on conditions of 0 m, 0.5 m, 1 m, 1.5 m, and 2 m fissure intervals are analyzed by creating a three-dimensional numerical model. The stress distribution and deformation laws of the roadway under mining disturbance are obtained. The results show that when the fissure interval is 1 m, the peak value of the horizontal stress reaches 10 12 MPa, and the stress concentration factor is 1.8 2.2, which promotes fracture expansion and transfixion and controls plastic damage development on both sides of a fracture. The elastic strain energy of the reused roadway is reduced to 32.7% of the peak value. The deformation of the roof is coordinated and deformed. It is helpful for the compound soft rock strata to fall and plug the area, forming a stable composite reused roadway surrounding the rock structure. A 1 m presplitting fissure interval is adopted for field testing, and the monitoring results show that 0 3.0 m behind the mining face, presplitting fissures will be connected and begin to fall. Moreover, 3.0 6.0 m behind the mining face, compound soft rock strata will fall and plug the area fully, forming a reused roadway structure. Severe deformation of reused roadway was reduced, and the stability of surrounding rock was improved by implementing the roof presplitting approach.